Leonardo da Vinci : the genius who defined the Renaissance - Phillips, John. (Washington, D.C. : National Geographic, 2006)
Examines the life of Renaissance genius Leonardo da Vinci, discussing his inquiries and accomplishments in art and various fields of science.
"A Marshall edition"--P. facing t.p.
Includes bibliographical references (p. 62) and index.
Accelerated Reader AR
Keywords: Leonardo, -- da Vinci, -- 1452-1519 -- Juvenile literature; Artists -- Italy -- Biography -- Juvenile literature; Scientists -- Italy -- Biography -- Juvenile literature